Space production, housing and real estate circuit in Fortaleza-CE: temporality and spatiality in the valuing southeast axis of the metropolis - Elizete de Oliveira Santos (2015)
The research discusses the different forms of housing production as necessary mediation between the space production dynamics and characteristics of the formal real estate circuit in the valuing southeast axis of Fortaleza metropolis, taking as a case study the Sapiranga/CoitÃ while conflict sector in the metropolis. The analysis object was studied based on the theoretical and methodological foundations of the social production of space theory. The methodology included documentary research (plant allotments and housing estates, slum mapping, urban and environmental legislation), statistics (data of IVV, ITBI, construction permits, dwell up and ARTs for residential developments), field work and interviews, gathering a database with qualitative and quantitative indicators at different spatial and temporal scales, from the definition of themes, processes and variables in the methodological matrix. This is on the assumption that there are different social logics of access to urban land and various agents of housing production that support specific forms of housing production. In the particular context of brazilian metropolises in contemporary times, the three forms of housing production are: production by the formal residential real estate circuit; production by the State; and production by informal residential real circuit. These forms of production are intertwined in reality through agendas, strategies and projects that sometimes come together and sometimes come into conflict. It defends the thesis that the formal real state expansion in conflict areas in the metropolis depends on the creation of a space production logic guided by differentiation strategies (location, product, construction, price, "concept" housing, target public etc.) and links with the State and the market to ensure the insulation in the proximity. The pair social distancing / spatial proximity supports the notion of socio-fragmentation, which approaches the idea of fractal segregation standard, fundamental concepts in this research. In the case study analyzed, the differentiation strategies were amalgamated in the constitution of the product horizontal gated community in the 1990s, making it the "brand" of the southeast sector. While urban form, the horizontal gated community contains processes and production space logical that give rise to it, generating in Sapiranga/CoitÃ a cumulative result of intense fragmentation in response to individual choices of investment by entrepreneurs and buyers.